Directed evolution of nucleotide-based libraries using lambda exonuclease - Bee Nar Lim; Yee Siew Choong; Asma Ismail; Jörn Glökler; Zoltán Konthur; Theam Soon Lim (BioTechniques)
Directed evolution of nucleotide libraries using recombination or mutagenesis is an important technique for customizing catalytic or biophysical traits of proteins. Conventional directed evolution methods, however, suffer from cumbersome digestion and ligation steps. Here, we describe a simple method to increase nucleotide diversity using single-stranded DNA (ssDNA) as a starting template. An initial PCR amplification using phosphorylated primers with overlapping regions followed by treatment with lambda exonuclease generates ssDNA templates that can then be annealed via the overlap regions. Double-stranded DNA (dsDNA) is then generated through extension with Klenow fragment. To demonstrate the applicability of this methodology for directed evolution of nucleotide libraries, we generated both gene shuffled and regional mutagenesis synthetic antibody libraries with titers of 2×108 and 6×107, respectively. We conclude that our method is an efficient and convenient approach to generate diversity in nucleic acid based libraries, especially recombinant antibody libraries.